Defects of poetry with reference to the first Persian rhetorical and literary writings - Mojahed Gholami (مطالعات زبانی و بلاغی)
After works such as Talkhis and Motowal, the three sciences of rhetoric were separated from each other, and the discussion about the defects of verse eloquence in Arabic and Persian rhetorical books was definitively placed in the introduction to the section on "Máāni" (meaning). Prior to that, the authors of Persian rhetorical and literary books such as the authors of Qābūs-nāma, Tarjomān ol-Balāqeh and Hadaiq ol-Sehr fi Daqāyeq ol-Sher have sporadically pointed out some factors of the defectiveness of poetry.. The author of Al-mojam fi Ma’āir Ashār ol-ájam took the initiative and dedicated a separate part of his book to introduce and analyze the defects of poetry and provided examples of Persian poetry for these defects. It is thus asserted that, eulogy and simplicity were the dominant modes in the first period of rhetorical compositions in Persian language, which coincides with the flourishing of Khorāsāni style. Therefore, the defects that are listed for poetry are consistent with the common style of composition in that period and offer a sound criticism. However, in the later periods, when critical texts were reduced to a rewriting of the rhetorical books of the first generation, the defects of poetry found in rhetorical treatises were no longer an accurate scale for criticizing Persian poetry, which had itself undergone changes in the dominant forms. In this analytical-descriptive study using library sources, the defects of Persian poetry were extracted and analyzed by focusing on credible pioneering rhetorical and literary books. The importance of this work lies in the fact that, in Persian literary tradition, "criticism" has been mainly equal to "technical criticism," which implies understanding the delicacies and defects of poetry and distinguishing good poetry from bad poetry.